Acquired Resistance to Severe Ethanol Stress in Saccharomyces cerevisiae Protein Quality Control - Yoshida, Masashi (Appl Environ Microbiol, 2021)
Acute severe ethanol stress (10% [vol/vol]) damages proteins and causes the intracellular accumulation of insoluble proteins in Saccharomyces cerevisiae. On the other hand, a pretreatment with mild stress increases tolerance to subsequent severe stress, which is called acquired stress resistance. It currently remains unclear whether the accumulation of insoluble proteins under severe ethanol stress may be mitigated by increasing protein quality control (PQC) activity in cells pretreated with mild stress. In the present study, we examined the induction of resistance to severe ethanol stress in PQC and confirmed that a pretreatment with 6% (vol/vol) ethanol or mild thermal stress at 37°C significantly reduced insoluble protein levels and the aggregation of Lsg1, which is prone to denaturation and aggregation by stress, in yeast cells under 10% (vol/vol) ethanol stress. The induction of this stress resistance required the new synthesis of proteins; the expression of proteins comprising the bichaperone system (Hsp104, Ssa3, and Fes1), Sis1, and Hsp42 was upregulated during the pretreatment and maintained under subsequent severe ethanol stress. Since the pretreated cells of deficient mutants in the bichaperone system (fes1Δ hsp104Δ and ssa2Δ ssa3Δ ssa4Δ) failed to sufficiently reduce insoluble protein levels and Lsg1 aggregation, the enhanced activity of the bichaperone system appears to be important for the induction of adequate stress resistance. In contrast, the importance of proteasomes and aggregases (Btn2 and Hsp42) in the induction of stress resistance has not been confirmed. These results provide further insights into the PQC activity of yeast cells under severe ethanol stress, including the brewing process. IMPORTANCE Although the budding yeast S. cerevisiae, which is used in the production of alcoholic beverages and bioethanol, is highly tolerant of ethanol, high concentrations of ethanol are also stressful to the yeast and cause various adverse effects, including protein denaturation. A pretreatment with mild stress improves the ethanol tolerance of yeast cells; however, it currently remains unclear whether it increases PQC activity and reduces the levels of denatured proteins. In the present study, we found that a pretreatment with mild ethanol upregulated the expression of proteins involved in PQC and mitigated the accumulation of insoluble proteins, even under severe ethanol stress. These results provide novel insights into ethanol tolerance and the adaptive capacity of yeast. They may also contribute to research on the physiology of yeast cells during the brewing process, in which the concentration of ethanol gradually increases.